Relative Leg Press Strength Related to Basal Metabolic Rate (BMR), Body Mass, And Body Fat in Female University Students: Implications for The Prescription of Exercise - Fauzi Antoni, Muhamad; Damayanti, Enarnimas Dwi Ratna; Suyoko, Andri; Samudra, Fajar Eka; Andriana, Laily Mita; Yudhistira, Dewangga (Universitas Negeri Semarang, 2025)
Introduction: Muscle strength affects metabolic activity and overall well-being, making it a critical component of physical fitness. Objectives: This study examines the relationship between university students' body weight, body fat, leg press strength, and Basal Metabolic Rate (BMR). Method: This study used a cross-sectional analytical design, selected using the purposive sampling technique with comprising female undergraduate students, sport coaching education enrolled in the Faculty of Sports Science at Surabaya State University, 56 participants with the following characteristics: who were aged (17.4 ± 2.7 years), had a height of (152.5 ± 29.47) cm, and had a weight of (55.15 ± 11.34 kg). Result: The results showed that there was a positive correlation between Basal Metabolic Rate (BMR) and leg press strength (r = 0.283, p = 0.034), indicating that greater lower body strength may help increase metabolism. In contrast, there was no significant correlation between body mass with leg press strength (r = 0.197, p = 0.146) and body fat with leg press strength (r = -0.111, p = 0.417), possibly due to individual differences in muscle distribution and fat storage. Conclusion: These findings emphasize the importance of strength training in improving weight control and metabolic health, especially in females. The study additionally highlights the necessity of additional investigation to gain a deeper comprehension of the mechanisms underlying these relationships and to explore other contributing factors. Overall, this study tells fitness experts how important a customized strength training program is for improving the metabolism and physical health of female college students.